2015 12th International Conference on Fuzzy Systems and Knowledge Discovery (FSKD) 2015
DOI: 10.1109/fskd.2015.7382063
|View full text |Cite
|
Sign up to set email alerts
|

Multigranulation with different grades rough set in ordered information system

Abstract: The the graded rough set and multi-granulation rough set are two significant extended rough set models, both constructed on the the indiscernibility relations. The purpose of this paper is to study the good points of graded rough set in the multi-granulation environment which in different granule have different grades in ordered information system. Three new types multi-granulation with different grades rough set models are proposed, which include optimistic multi-granulation with different grades, pessimistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…References [13][14][15][16][17] discussed GRS in a multi-granulation environment. Moreover, for GRS, it has been studied that the equivalence relation has been extended to the dominance relation [13,14], the limited tolerance relation [17] and so forth [10,11]. In general, all these aforementioned studies have naturally contributed to the development of GRS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…References [13][14][15][16][17] discussed GRS in a multi-granulation environment. Moreover, for GRS, it has been studied that the equivalence relation has been extended to the dominance relation [13,14], the limited tolerance relation [17] and so forth [10,11]. In general, all these aforementioned studies have naturally contributed to the development of GRS.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the research reported in References [5,[13][14][15][16][17], intuitionistic fuzzy sets (IFS) are also a theory which describe uncertainty [18]. IFS consisting of a membership function and a non-membership function are commonly encountered in uncertainty, imprecision, and vagueness [18].…”
Section: Introductionmentioning
confidence: 99%